2018
DOI: 10.1109/tits.2017.2701846
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated Evaluation of Automated Vehicles in Car-Following Maneuvers

Abstract: Abstract-The safety of Automated Vehicles (AVs) must be assured before their release and deployment. The current approach to evaluation relies primarily on (i) testing AVs on public roads or (ii) track testing with scenarios defined in a test matrix. These two methods have completely opposing drawbacks: the former, while offering realistic scenarios, takes too much time to execute; the latter, though it can be completed in a short amount of time, has no clear correlation to safety benefits in the real world. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
156
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 192 publications
(156 citation statements)
references
References 35 publications
0
156
0
Order By: Relevance
“…It was found that the evaluation time of a car following scenario can be reduced by up to a factor of 100,000, and for a lane change scenario by up to 20,000 [6], [13]. In [2], importance sampling was used to evaluate an adaptive cruise control system.…”
Section: A Validation Of Avs Based On Scenariosmentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that the evaluation time of a car following scenario can be reduced by up to a factor of 100,000, and for a lane change scenario by up to 20,000 [6], [13]. In [2], importance sampling was used to evaluate an adaptive cruise control system.…”
Section: A Validation Of Avs Based On Scenariosmentioning
confidence: 99%
“…The general disadvantage of variance reduction techniques is their requirement of prior knowledge in order to shape the probability distribution used for sampling. Often this data is taken from accident databases or naturalistic driving trails [6]. This runs the risk however to exclude scenarios that emerge due to the new automation technology, which is often not considered in accident databases or naturalistic driving trails.…”
Section: A Validation Of Avs Based On Scenariosmentioning
confidence: 99%
“…We use ξ i to denote a realization of the random vector ξ. In Accelerated Evaluation approaches [1], [5], [7], the traffic environment is considered an uncertainty for the AV system under study and is represented by ξ.…”
Section: A Av Safety Evaluation Settingmentioning
confidence: 99%
“…By properly We gratefully acknowledge the support from the National Science Foundation under grants CAREER CMMI-1653339/1834710, IIS-1849280, and IIS-1849304. 1 integrating the Monte Carlo approach into the modeling scheme, researchers have been able to estimate the risk from driving situations based on control and trajectory prediction [3], [4] and corner cases in various driving scenarios [1], [5].…”
Section: Introductionmentioning
confidence: 99%
“…Input: SM and offline generated library Output: Customized library 1 Step 1: Observe f with initial testing scenarios. (Sec 4.A) 2 Step 2: while the stop criteria (e.g., budget or estimation precision) is not satisfied do 3 Step 2.1: Obtain the estimationf (Sec 4.B); 4 Step 2.2: Update SM and library (Sec 4.C); 5 Step 2.3: Decide next iteration of testing scenarios (Sec 4.D); 6 Step 2.4: Observe f by testing the CAV with new scenarios; 7 end…”
Section: B Bayesian Optimization Schemementioning
confidence: 99%